Nonlinear Delay Discrete Inequalities and Their Applications to Volterra Type Difference Equations. (21st January 2010) - Wu, Yu; Li, Xiaopei; Deng, Shengfu
Abstract : Delay discrete inequalities with more than one nonlinear term are discussed, which generalize some known results and can be used in the analysis of various problems in the theory of certain classes of discrete equations. Application examples to show boundedness and uniqueness of solutions of a Volterra type difference equation are also given.